2018
DOI: 10.1063/1.5004578
|View full text |Cite
|
Sign up to set email alerts
|

Lessons on electronic decoherence in molecules from exact modeling

Abstract: Electronic decoherence processes in molecules and materials are usually thought and modeled via schemes for the system-bath evolution in which the bath is treated either implicitly or approximately. Here we present computations of the electronic decoherence dynamics of a model many-body molecular system described by the Su-Schrieffer-Heeger Hamiltonian with Hubbard electron-electron interactions using an exact method in which both electronic and nuclear degrees of freedom are taken into account explicitly and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 52 publications
2
40
2
Order By: Relevance
“…However, the environment for the molecular motion (e.g., solvent) may have a large inuence on the nonadiabatic polaritonic dynamics through ultrafast electronic decoherence processes. [39][40][41] We introduce an external environment…”
Section: Effects Of the External Environmentmentioning
confidence: 99%
“…However, the environment for the molecular motion (e.g., solvent) may have a large inuence on the nonadiabatic polaritonic dynamics through ultrafast electronic decoherence processes. [39][40][41] We introduce an external environment…”
Section: Effects Of the External Environmentmentioning
confidence: 99%
“…Even when this condition is not strictly satisfied, the pure-dephasing effects may still be the dominant effect when the environment dynamics is non-resonant with the transition frequencies of the system such that the dissipation is much slower compared to pure-dephasing effects. For this reason, the pure-dephasing limit has been useful in describing electronic decoherence in molecules [4,6], elastic electron-phonon interaction in solid state systems, loss of quantum interference [19], line shape in spectroscopic measurements [20], vibrational dephasing in solvents [29] and the central spin problem [18].…”
Section: Pure Dephasing Dynamicsmentioning
confidence: 99%
“…The inevitable interaction between a quantum system with its surrounding environment leads to decoherence [1][2][3][4][5][6]. The decoherence occurs because such interaction leads to systembath entanglement that turns a pure system state to a statistical mixture of states.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] The nuclei act as an environment that induces a loss of phase relationship between the electronic states. Understanding the mechanisms for electronic decoherence is of vital importance for understanding the ground-and excited-state dynamics of molecules, 5,6,8,9 for developing accurate approximations to model correlated electron-nuclear dynamics 11,12 and for preserving electronic coherence that can subsequently be used to enhance molecular functions. 13 A fundamental question that arises in this context is what is the mutual influence of electron-electron interactions and electronic decoherence.…”
mentioning
confidence: 99%
“…14 More precisely, whether decoherence can induce changes in the electronic correlation and, conversely, whether electron-electron interactions can modify the electronic decoherence dynamics. In a recent exact numerical study of electronic decoherence for the Su-Schrieffer-Heeger (SSH) Hamiltonian amended by the Hubbard electronrepulsion term, 6 it was shown that while the electron-electron interactions can induce a significant change of the electronic decoherence by introducing and modifying avoided crossings among the Potential Energy Surfaces (PESs), they do not a) ignacio.franco@rochester.edu influence the decoherence when the dynamics is puredephasing in nature. That is, when the nuclei do not introduce significant transitions among electronic diabatic states.…”
mentioning
confidence: 99%